Accelerated avian invasion into the Mediterranean region endangers biodiversity and mandates international collaboration. Issue 6 (21st March 2022) - Magory Cohen, Tali; Hauber, Mark E.; Akriotis, Triantaphyllos; Crochet, Pierre‐André; Karris, Georgios; Kirschel, Alexander N. G.; Khoury, Fares; Menchetti, Mattia; Mori, Emiliano; Per, Esra; Reino, Luís; Saavedra, Susana; et al.
Abstract: Despite posing a serious threat to global biodiversity, national and international management efforts have not been able to limit the spread of most invasive species. In highly dispersive species, local invasions may be followed by regional range expansion that crosses international borders. In such cases, independent management efforts of the invading population may be futile unless international collaboration is practiced. We focus on the ongoing human‐mediated invasion of the common myna Acridotheres tristis into the Mediterranean basin, a region rich in overall numbers of species and endemic species, where common mynas have been introduced into a handful of countries. Some introductions were followed by subsequent range expansions into neighbouring countries. This species poses major threats to the biodiversity of the Mediterranean which is already susceptible to biodiversity loss as the result of ongoing land use and climate changes. Without action, this species and possibly others similar to it, could have severe consequences for native ecosystems. Policy implications . Given the regional scope of its invasion in the Mediterranean basin, common myna management requires an international collaboration to successfully prevent additional introductions and range expansions and to avoid accelerating threats to Mediterranean biodiversity, already at risk as a result of ongoing changes in land use and climate. We argue that international reciprocal transfer of information and the development of regional mitigation are essential for the successful management of the invasion of the common myna and other species into the Mediterranean. Abstract : Given the regional scope of its invasion in the Mediterranean basin, common myna management requires an international collaboration to successfully prevent additional introductions and range expansions and to avoid accelerating threats to Mediterranean biodiversity, already at risk as a result of ongoing changes in land use and climate. We argue that international reciprocal transfer of information and the development of regional mitigation are essential for the successful management of the invasion of the common myna and other species into the Mediterranean. Resumo: Apesar das espécies invasoras representarem uma séria ameaça à biodiversidade global, os esforços de gestão nacionais e internacionais não têm sido capazes de limitar a sua propagação. No caso das espécies com elevada capacidade de dispersão, as invasões locais podem ser seguidas de uma expansão de alcance regional, podendo atravessar as fronteiras internacionais. Nesses casos, esforços independentes que visem a gestão das populações invasoras podem ser inúteis, a menos que haja uma colaboração internacional. Este estudo foca‐se na invasão em curso do mainá‐indiano (Acridotheres tristis) na bacia mediterrânica, uma região com elevada riqueza específica e elevado número de espécies endémicas, onde a espécie foi introduzida em diversos países. Algumas destas introduções foram seguidas por expansões que chegaram a territórios de países vizinhos. Esta espécie representa uma ameaça para a biodiversidade do Mediterrâneo, que já é susceptível de perda de biodiversidade devido às alterações em curso do uso do solo e do clima. Na ausência de políticas concretas, tanto esta espécie, como possivelmente outras semelhantes, poderão vir a ter consequências graves para os ecossistemas naturais. Implicações políticas: Dado o âmbito regional da invasão do mainá‐indiano na bacia mediterrânica, a sua gestão requer uma colaboração internacional para evitar novas introduções e expansões importantes, evitando assim possíveis ameaças à biodiversidade mediterrânica, já em risco como resultado das mudanças em curso no uso do solo e no clima. Defendemos que a transferência recíproca de informação internacional e o desenvolvimento de medidas de mitigação de âmbito regional são essenciais para a gestão bem‐sucedida da invasão do mainá‐indiano e de outras espécies no Mediterrâneo.